DEVELOPMENT AND CHARACTERIZATION OF POLY(OXY-1,4-PHENYLENESULFONYL-1,4-PHENYLENE) FOR PROTON EXCHANGE MEMBRANES - PACHECO LANCHEROS, ANDRÉS; LOMBANA PUERTA, AURA; REALPE JIMÉNEZ, ÁLVARO; MENDOZA BELTRAN, DINA; ACEVEDO MORANTES, MARÍA TERESA (Journal of Applied Engineering Science, 2021)
Proton Exchange Membranes (PEMs) are materials developed with a focus on high-performance, low-cost features to achieve promising fuel cell technology in stationary, portable, and transportation facilities. In this study, we synthesized membranes from Poly (oxy-1,4-phenylenesulfonyl-1,4-phenylene) (PES) sulfonated with modification by adding nanoclay to improve the mechanical properties of PEMs. The sulfonation time and the concentration of nanoclays directly favored properties such as contact angle, water absorption, porosity, and mechanical properties. However, a higher concentration of nanoclays (e.g., 10% by weight) damages the mechanical properties of PES membranes specifically. The membrane with 5% by weight of nanoclay and a sulfonation time of 2 h achieved the best performance.
Keywords: fuel cell, membrane sulfonation, polyethersulfone membrane, proton exchange membrane, nanoclay